Contributions of PBP 5 and dd-Carboxypeptidase Penicillin Binding Proteins to Maintenance of Cell Shape in Escherichia coli - Nelson, David E. (American Society for Microbiology, 2001)
Escherichia coli has 12 recognized penicillin binding proteins (PBPs), four of which (PBPs 4, 5, and 6 and DacD) have dd-carboxypeptidase activity. Although the enzymology of the dd-carboxypeptidases has been studied extensively, the in vivo functions of these proteins are poorly understood. To explain why E. coli maintains four independent loci encoding enzymes of considerable sequence identity and comparable in vitro activity, it has been proposed that the dd-carboxypeptidases may substitute for one another in vivo. We tested the validity of this equivalent substitution hypothesis by investigating the effects of these proteins on the aberrant morphology of ΔdacA mutants, which produce no PBP 5. Although cloned PBP 5 complemented the morphological phenotype of a ΔdacA mutant lacking a total of seven PBPs, controlled expression of PBP 4, PBP 6, or DacD did not. Also, a truncated PBP 5 protein lacking its amphipathic C-terminal membrane binding sequence did not reverse the morphological defects and was lethal at low levels of expression, implying that membrane anchoring is essential for the proper functioning of PBP 5. By examining a set of mutants from which multiple PBP genes were deleted, we found that significant morphological aberrations required the absence of at least three different PBPs. The greatest defects were observed in cells lacking, at minimum, PBPs 5 and 6 and one of the endopeptidases (either PBP 4 or PBP 7). The results further differentiate the roles of the low-molecular-weight PBPs, suggest a functional significance for the amphipathic membrane anchor of PBP 5 and, when combined with the recently determined crystal structure of PBP 5, suggest possible mechanisms by which these PBPs may contribute to maintenance of a uniform cell shape in E. coli.